2019
DOI: 10.1016/j.mad.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants linked with physical, cognitive and psychological frailty: Analysis of candidate biomarkers and markers derived from the MARK-AGE study

Abstract: Frailty among elderly people leads to an increased risk for negative health outcomes. To prevent frailty, we need a better understanding of the underlying mechanisms and early detection of individuals at risk. Both may be served by identifying candidate (bio)markers, i.e. biomarkers and markers, for the physical, cognitive, and psychological frailty domains. We used univariate (Rank-ANOVA) and multivariate (elastic net) approaches on the RASIG study population (age range: 35-74 years, n = 2220) of the MARK-AGE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 47 publications
2
40
0
Order By: Relevance
“…However, other analyses focused on elderly women from the WHAS I cohort [64,70] or participants recruited from Geriatric Day programs [64,70] did not find any correlation between changes in vitamin E and frailty. Similar inconsistent results were found in studies for vitamin A and other antioxidants such as carotenoids [70,71], although recent data from the European study to establish biomarkers of human ageing (MARK-AGE) study shows that physical frailty is significantly associated with lower levels of carotenoids such as α-carotene, β-carotene and βcryptoxanthin [72]. In this sense, it should be noted that serum vitamin levels can be easily altered with diet or during disease, facts that might complicate the interpretation of these results.…”
Section: Oxidative Stress In Physical Frailtysupporting
confidence: 54%
See 2 more Smart Citations
“…However, other analyses focused on elderly women from the WHAS I cohort [64,70] or participants recruited from Geriatric Day programs [64,70] did not find any correlation between changes in vitamin E and frailty. Similar inconsistent results were found in studies for vitamin A and other antioxidants such as carotenoids [70,71], although recent data from the European study to establish biomarkers of human ageing (MARK-AGE) study shows that physical frailty is significantly associated with lower levels of carotenoids such as α-carotene, β-carotene and βcryptoxanthin [72]. In this sense, it should be noted that serum vitamin levels can be easily altered with diet or during disease, facts that might complicate the interpretation of these results.…”
Section: Oxidative Stress In Physical Frailtysupporting
confidence: 54%
“…Among them, recent studies have detected the link between cognitive frailty and oxidative stress. Thus, the MARK-AGE study has recently found that lower levels of two carotenoids (i.e., zeaxanthin and βcriptoxanthin) were associated with cognitive frailty and could predict the risk of developing frailty at cognitive level [72]. Furthermore, the same study also suggested that a decreased level of α-tocopherol is a biomarker for cognitive frailty.…”
Section: Oxidative Stress In Cognitive Frailtymentioning
confidence: 92%
See 1 more Smart Citation
“…In accord with our results, a cohort study of 2,198 noninstitutionalized men and women in Spain reported that serum high uric acid concentrations were associa ted with incident frailty (GarcíaEsquinas et al, 2016). By contrast, data from the Randomly recruited Age Stratified Individuals from the General population (RASIG) group within the bioMARKers of human AGEing (MARKAGE) study in Europe (n = 2,220 participants, aged 35-74 years, observed lower levels of antioxidants including βcryptoxanthin and zeaxanthin among individuals identified as frail based on the physi cal, cognitive, and psychological domains of frailty (Rietman et al, 2018). A crosssectional multicenter study in Japan, involving a multigenerational cohort of 2,121 grandmothers (65 years and older), investigated the association between dietary TAC and prevalence of frailty (Kobayashi et al, 2014).…”
Section: Discussionmentioning
confidence: 98%
“…The consumption of diet rich in fruits and vegetables as well as the modification of nutritional habits and lifestyle associates with higher oxocarotenoid levels in plasma and a lower risk of age-related diseases and AD [13]. Conversely, in the MARKAGE study, lower levels of β-cryptoxanthin and zeaxanthin were observed in the cognitively frail [14].…”
Section: Introductionmentioning
confidence: 92%